Safety of Men With Small and Medium Abdominal Aortic Aneurysms Under Surveillance in the NAAASP. Issue 11 (12th March 2019) - Oliver-Williams, Clare; Sweeting, Michael J.; Jacomelli, Jo; Summers, Lisa; Stevenson, Anne; Lees, Tim; Earnshaw, Jonothan J.
Abstract : Background: Population screening for abdominal aortic aneurysm (AAA) has commenced in several countries, and has been shown to reduce AAA-related mortality by up to 50%. Most men who screen positive have an AAA <5.5 cm in diameter, the referral threshold for treatment, and are entered into an ultrasound surveillance program. This study aimed to determine the risk of ruptured AAA (rAAA) in men under surveillance. Methods: Men in the National Health Service AAA Screening Programme who initially had a small (3–4.4 cm) or medium (4.5–5.4 cm) AAA were followed up. The screening program's database collected data on ultrasound AAA diameter measurements, dates of referral, and loss to follow-up. Local screening programs recorded adverse outcomes, including rAAA and death. Rupture and mortality rates were calculated by initial and final known AAA diameter. Results: A total of 18 652 men were included (50 103 person-years of surveillance). Thirty-one men had rAAA during surveillance, of whom 29 died. Some 952 men died of other causes during surveillance, mainly cardiovascular complications (26.3%) and cancer (31.2%). The overall mortality rate was 1.96% per annum, similar for men with small and medium AAAs. The rAAA risk was 0.03% per annum (95% CI, 0.02%–0.05%) for men with small AAAs and 0.28% (0.17%–0.44%) for medium AAAs. The rAAA risk for men with AAAs just below the referral threshold (5.0–5.4 cm) was 0.40% (0.22%–0.73%). Conclusions: The risk of rAAA under surveillance is <0.5% per annum, even just below the present referral threshold of 5.5 cm, and only 0.4% of men under surveillance are estimated to rupture before referral. It can be concluded that men with small and medium screen-detected AAAs are safe provided they are enrolled in an intensive surveillance program, and that there is no evidence that the current referral threshold of 5.5 cm should be changed.